Pendidikan Berbasis Malakah Kurikulum Pendidikan Perspektif Ibnu Khaldun - Rusydi, Rusydi (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2021)
Ibn Khaldun believed that economic progress and civilization are intertwined with the progress of education. He believed that "sciences are becoming more and more in line with the magnitude of prosperity and the high level of civilization," which means that as economic and socio-cultural development advances, this will naturally encourage the development of various kinds of knowledge and community expertise. As prosperity increases, people's income increases, and this leads to progress in education. Ibn Khaldun was a figure who placed great importance on education. He believed that education was a tool that could help people live a good life in society. According to his view of humans as creatures who must be educated, in order to carry out their social functions in the midst of society, education was necessary to develop the skills and expertise (known as "al-malakah") in a particular field. Ibn Khaldun believed that everyone has the potential to research and understand a problem just like a scientist. However, the potential of "al-malakah" cannot be owned by everyone, except after he really understands and explores a particular discipline. The ultimate goal of education, in Ibn Khaldun's view, was to develop these skills and expertise in a particular field.